Best Practices for Software Maturity Improvement: A GÉANT Case Study - Walter, Bartosz; Marović, Branko; Garnizov, Ivan; Wolski, Marcin; Todosijevic, Andrijana (Communications in Computer and Information Science, 2020)
Maturity models for software indicate the key areas that contribute to quality improvements. They usually combine technical, organisational and human aspects relevant for effective software development, to focus the efforts and draw the direction for optimisations. In this paper, we present the process of defining best practices that support the GÉANT Software Maturity Model (GSMM), aligned to the needs of a distributed, innovation-driven, pan-European organisation. Based on the identification of specific goals relevant for GÉANT and a preliminary maturity assessment, we created a catalogue of best practices that help the software teams to attain the goals defined in the GSMM.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Best practices; Maturity evaluation; Software process improvement; SPI

Monitoring the Adoption of SPI-Related Best Practices. An Experience Report - Walter, Bartosz; Marović, Branko; Garnizov, Ivan; Wolski, Marcin; Todosijevic, Andrijana (Communications in Computer and Information Science, 2021)
Software Process Improvement requires significant effort related not only to the identification of relevant issues and providing adequate response to them, but also to the implementation and adoption of the changes. Best practices provide recommendations to software teams on how to address the identified objectives in practice, based on aggregated experience and knowledge. In the paper, we present the GÉANT experience and observations from the process of adopting the best practices, and present the setting we have been using.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Best practices; Software maturity evaluation; Software process improvement; SPI monitoring

Supporting Product Management Lifecycle with Common Best Practices - Walter, Bartosz; Jolevski, Ilija; Garnizov, Ivan; Arsovic, Andjela (Communications in Computer and Information Science, 2023)
Product Lifecycle Management is a process that helps projects to pass through various phases of software development and maintenance. Since phases are usually associated with entry- and exit-criteria that could be considered onerous or excessively effort-prone, implementation of PLM poses various risks. In this paper we show how Common Best Practices could support the software teams in meeting PLM requirements and facilitate smoother transition between phases.
CRIS-Team Scopus Importer:2023-10-06
Keywords: best practices; product lifecycle management; software process improvement

Two Case Studies on Implementing Best Practices for Software Process Improvement - Walter, Bartosz; Marović, Branko; Garnizov, Ivan; Wolski, Marcin; Todosijevic, Andrijana (Communications in Computer and Information Science, 2022)
Software Process Improvement requires significant effort related not only to the identification of relevant issues and providing an adequate response to them but also to the implementation and adoption of the changes. Best practices provide recommendations to software teams on how to address the identified objectives in practice, based on aggregated experience and knowledge. In the paper, we present the GÉANT experience and observations from the process of adopting the best practices and present the setting we have been using.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Best practices; Software maturity evaluation; Software Process Improvement; SPI monitoring